Identifikasi Protozoa pada Darah dan Saluran Pencernaan Biawak Air (Varanus salvator) - Azizah Bilqis Nurkarimah; Mufasirin Mufasirin; Ratna Damayanti; Lucia Tri Suwanti; Boedi Setiawan; Endang Suprihati (Journal of Parasite Science (JoPS), 2020)
The aim of this research is to identify the variaous of protozoa in the bloodanddigestive tract on water monitor lizard (Varanus salvator) was captured in Sidoarjo, East Java. This research was taken on March until June 2019. This research used a non-experimental method through an observation study. As many as 50 water monitor lizard were used this research and examined at the Laboratory of Parasitology, Faculty of Veterinary Medicine, Universitas Airlangga.The samples of this research were made in thin blood smear using Giemsa stain, while fecal examination using native method, sucrose flotation, and modified Ziehl-Neelsen stain.The results showed that two various of protozoa found were single infection. Observations on the blood was obtained Haemogregarina sp. (14%) and observations of feces obtained Eimeria sp. (2%). The conclusion of this research indicate that type of protozoa was Haemogregarina sp. and Eimeria sp. were found on water monitor lizard(Varanus salvator).